What Are the Causes of Death among Patients Admitted to a Contemporary Tertiary-Level Cardiology Department? An Analysis of 10 Years of Morbidity and Mortality Meetings - Chun Shing Kwok; Jacopo Tafuro; Chun Wai Wong; Sadie Bennett; Donah Zachariah; Diane Barker; Adrian Morley-Davies; Duwarakan Satchithananda; Mark Gunning; Josip A. Borovac (Pathophysiology, 2023)
Despite the efforts to deliver the best evidence-based care, in-hospital death is an inevitable event among some patients hospitalized in cardiology departments. We conducted a retrospective evaluation of mortality events from inpatient admissions to the cardiology department between 2010 and 2019. Data were collected from morbidity and mortality meeting presentations that evaluated comorbidities, medical history, treatments, and causes of death for the overall cohort and according to age group and sex. There were 1182 registered deaths. The most common causes of death among patients were acute myocardial infarction (AMI, 53.0%), heart failure (HF, 11.7%), cardiac arrest (CA, 6.6%), HF with complication/defined cardiomyopathy (6.3%), and sepsis (4.4%). We observed a decline in deaths from AMI from 61.9% in 2010 to 46.7% in 2019, while there was a clear increase in deaths from HF (11.1% in 2010 to 25.9% in 2019). Compared to patients ≥65 years, younger patients were more likely to have died from CA (15.7% vs. 4.3%, p < 0.001) and other cardiac reasons (3.0% vs. 0.4%, p < 0.001). The majority of deaths were due to AMI, HF, and CA. We observed a significant declining trend in the proportion of deaths due to AMI in recent years, with an increase in deaths due to HF.